Hydrops fetalis due to Bart hemoglobinopathy at Ramathibodi Hospital (1978-1987): a 10-year review. - P. O-Prasertsawat (2018)
This was a retrospective case-control study of hydrops fetalis due to Bart hemoglobinopathy at Ramathibodi Hospital between 1978-1987. The incidence was 0.61 per 1,000 deliveries. Hydrops fetalis tend to go into labour prematurely with smaller fetuses and larger placentae. When compared with the control group there were statistically significant differences in the history of previous perinatal loss and obstetric complications i.e. hypertensive disorder in pregnancy and postpartum hemorrhage. Early diagnosis and termination of pregnancy will avoid these complications.